Subhepatic inferior vena cava traumatisms.: Aspectos clínico-patológicos - Estrugo, Roberto (Cirugía del Uruguay, 1989)
1) Clin¡copathological aspects. Regarding the presenlation of 7 new cases authors revise jointly 22 <:ases of subhepatic inferior vena cava traumatisms (IVCT) published in national literature. They point out the low lesiona! frecuency with a progressive incidence increase.